REVIEW OF THE MORPHOLOGY OF TRIMERESURUS BROGERSMAI (SERPENTES: CIPERIDAE), A RARE PIVIPER OF SIMEULUE AND THE MENTAWAI ISLANDS, INDONESIA - Michael B Harvey; Irvan Sidik (Treubia, 2013)
Trimeresurus brongersmai is a rare pitviper from Simeulue and the Mentawai Islands. We comment on the morphology and examine new specimens from Siberut Island. The four new specimens differ morphologically from the eight specimens known previously. A distinctive banding pattern on the distal tail characterises T. brongersmai and the related species T. puniceus. Juveniles lack the distinctive projecting supraoculars of adult T. brongersmai and these scales apparently develop during ontogeny. We propose the new term â€œrostronasalâ€ for a large scale positioned between the rostral and nasal on each side of the snout in this species. In addition, we discuss several features of this species that were not mentioned in earlier accounts.